A pilot serosurvey of Babesia microti in Chinese blood donors. Issue 4 (26th March 2018) - Bloch, E. M.; Yang, Y.; He, M.; Tonnetti, L.; Liu, Y.; Wang, J.; Guo, Y.; Li, H.; Leiby, D. A.; Shan, H.; ,
Abstract : Background and Objectives: Babesia spp. are tick‐borne, intraerythrocytic protozoan parasites, several of which are transfusion‐transmissible. Transfusion‐transmitted babesiosis poses serious risk to a diverse patient population, including neonates, patients aged >50 years, the asplenic and the immunocompromised that are over‐represented among transfusion recipients. Despite reports of B. microti and B. venatorum in People's Republic of China (PRC), no surveillance of blood donors for Babesia has previously been undertaken. We sought to determine the rates of B. microti seroreactivity in a sample of blood donors in the PRC. Materials and Methods: A pilot serosurvey was conducted of community blood donors ( n = 1000) who donated July–August 2016 at Mudanjiang Blood Center (Heilongjiang Province) using indirect fluorescent antibody testing for antibodies against B. microti . The slides were prepared using B. microti ‐infected hamster blood. Samples that were initially positive to a titre of 64 were subjected to repeat IFA testing. Final seroreactivity was based on repeat reactivity to ≥64. Results: A total of 1000 individual donor samples were evaluated, comprising 888 whole blood and 112 platelet donations. Thirteen of 1000 (1·3%) donors were seroreactive for B. microti [8 (0·8%) and five (0·05%) at titres of 64 and 128, respectively]. Conclusion: Our preliminary findings support the need for expanded Babesia surveillance in Chinese blood donors, replete with molecular evaluation, to evaluate the risk to the blood supply.